2012
DOI: 10.1108/09590551211239837
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers' opposition motives to the modern retailing format in the Tunisian market

Abstract: PurposeThis study seeks to explore the issue of individual opposition to the organized retailing system in an emerging country. It aims to identify the motivations for rejecting such retail outlets as well as how the resistance that is generated expresses itself and to point out the amazing precocity of the emergence of this resistance in these developing countries.Design/methodology/approachIn‐depth interviews using the critical incident technique were conducted to explore the reasons for consumers' partial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Second, the traditional retailing sector (convenience stores and traditional corner shops) remains very attractive for the customers, thus putting further competitive pressure on the retail industry. Amine and Hendaoui Ben Tanfous (2012), consistently with Izberk-Bilgin (2008), highlighted this "Tunisian paradox". They put forward the idea that beside the perceived culture distance between the retailers' original country and the host country, as well as the common motives identified in Western economies, post-colonial and anti-globalisation movements motive local consumers to reject the modern retail format, though they are attracted by western products and the values associated with modernity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Second, the traditional retailing sector (convenience stores and traditional corner shops) remains very attractive for the customers, thus putting further competitive pressure on the retail industry. Amine and Hendaoui Ben Tanfous (2012), consistently with Izberk-Bilgin (2008), highlighted this "Tunisian paradox". They put forward the idea that beside the perceived culture distance between the retailers' original country and the host country, as well as the common motives identified in Western economies, post-colonial and anti-globalisation movements motive local consumers to reject the modern retail format, though they are attracted by western products and the values associated with modernity.…”
Section: Discussionsupporting
confidence: 54%
“…Emerging countries, where these features are largely absent, are becoming more and more attractive for the main actors in modern retailing, since they offer good prospects for growth, and return on investment. This is due to the enlargement of the middle class, especially in urban areas; the development of transport infrastructures and the improvement of per capita GDP (Amine & Hendaoui Ben Tanfous, 2012;Miotto & Parente, 2015). In this context, Tunisian distribution is to develop and modernise, by integrating contemporary techniques and responses to changing movements observed in industrialised countries (Prime, Abdelmajid, Obadia, & Dupuis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In view of this claim, there are some specific studies that have been conducted in relation to developing nations on their consumption dynamics. The study of Amine et al (2012), which revolves around consumers' opposition motives to the modern retailing format in Tunisia, found that when compared to developed nations, consumers in this context are prone to avoid and defect…”
Section: Religion In Developing Nations: Perspective On Consumptionmentioning
confidence: 99%
“…While this publication is now over a decade old, the current state of affairs in the world economy corroborates this projection. For example, Amine et al (2012) note that the main actors in modern retailing are now making incursions into emerging nations as these countries offer decent growth prospects and returns on investment which could be attributed to a number of developments such as improvements in gross development product and an increasing middle class. The same argument is made by Rihtaršič and Rihtaršič (2017) who claim that the globalisation, continuous migration of people, and access to information make the boundary between rural and urban populations rather blurred.…”
Section: Religion and Consumer Behaviour In The Twenty-first-century Developing Nationsmentioning
confidence: 99%
“…Beginning in the middle of 2000, the authors describe an emerging fourth wave in currently less industrialized countries such as Cambodia, Bolivia and sub-Saharan Africa. Several studies of retail internationalization exist for emerging markets such as Tunisia (Amine & Tanfous, 2012), Turkey and Morocco (Codron et al, 2004;Appel, 2014), South Africa (D'Haese & Van Huylenbroeck, 2005, Latin American countries such as Chile (Faiguenbaum et al, 2002;Reardon et al, 2007b), the four BRIC nations of Brazil (Alexander & De Lira and Silva, 2002), Russia (Lorentz & Hilmola, 2008), India (Reardon & Gulati, 2008;Akther & Equbal, 2012) and China (Cao & Pederzoli, 2013;Hardaker, 2017), the East Asian region as a whole (Larke, 2006), as well as a variety of South Asian states such as Vietnam (Hagen, 2002;Maruyama & Trung, 2007;FIiguié & Moustier, 2009;Nguyen et al, 2013) and Malaysia (Hassan et al, 2013). As far as Myanmar's retail trade is concerned, no academic studies exist to current knowledge of the author.…”
Section: Introductionmentioning
confidence: 99%